Investigation of anti-proliferative and antioxidative effects of some bis (?-amino) phosphinic acid derivatives - Dastan, Taner; Dastan, Sevgi Durna; Atas, Mehmet; Orek, Cahit; Koparir, Pelin; Parlak, Akif Evren; Cetin, Ahmet (Univ Karachi, 2016)
Aminophosphinic acids which are organophosphorus compounds widely investigated for potential production of antibacterial, antitumor and antiviral materials. In vitro antioxidant, cytotoxic and antimicrobial activities of synthesized novel compounds of 8 different bis(a-amino alkyl)phosphinic acids (4a-h) were investigated on MCF-7 breast adenocarcinoma cell and human umbilical vein endothelial cell (HUVEC) cultures. Malondialdehyde (MDA) levels were evaluated as an indication of lipid peroxidation in cell cultures for antioxidant capacities. In vitro antioxidant activities in cell cultures were determined by evaluating totals of antioxidant, oxidant, thiol levels and activities of paraoxanase, aryl esterase. It was found that 4c compound reduced MDA level significantly while 4a and 4g compounds increased MDA levels significantly compared to control. 4c compound was found most effective in reducing MDA levels by neutralizing reactive oxygen species to prevent cell damage while compounds 4c, 4f and 4h were found presenting adequate activity with other antioxidants. In vitro anti-proliferation was evaluated on MCF-7 and HUVEC cells using XTT to investigate anti-cancer potentials as therapeutics. Compounds 4c, 4e and 4f were exhibited better compared to others. Most compounds were found cytotoxic to both MCF-7 and HUVECs. Antimicrobial and antifungal activities were investigated by disc diffusion and compared to MICs of Gentamycin and Nystatin.
Keywords: anticancer; antimicrobial; bis phosphinic acids; cytotoxicity; oxidative stress